Modified-Power-Piston: Short-Incudial-Process-Vibroplasty and Simultaneous Stapedotomy in Otosclerosis. Issue 3 (March 2019) - Dejaco, Daniel; Riedl, David; Gottfried, Timo; Rasse, Thomas; Fischer, Natalie; Prejban, David; Koci, Viktor; Riechelmann, Herbert; Schmutzhard, Joachim; Keintzel, Thomas
Abstract : Objective: If mixed-hearing-loss (MHL) occurs in otosclerosis, hearing-aids (HA) in addition to conventional-stapedotomy (SDT) may be necessary. If otosclerosis progresses or technical or medical problems prevent use of HA, combining active-middle-ear-implants (AMEI) with SDT ("power-piston") may be considered. Previously, AMEI-coupling to the long-incudial-process was suggested. Here, a "modified-power-piston" surgery (mPP) coupling to the short-incudial-process was proposed, so no coupling over the positioned stapes-piston is required. We questioned whether mPP is as safe and effective as SDT. Methods: Otosclerotic patients with MHL and limited satisfaction with previously worn HA receiving mPP were retrospectively reviewed at two Austrian tertiary otologic referral centers. Patients, receiving stapedotomy, were case-matched for preoperative pure-tone averages (PTA), bone-conduction (BC-PTA), air-conduction (AC-PTA), and air-bone gap (ABG-PTA). Postoperative changes in BC-PTA and in AC-PTA and ABG-PTA were defined as safety- and as efficacy outcome parameter. Results: Of 160 patients, 14 received mPP and 14 stapedotomy. Preoperative findings were comparable (all p  = 1.000). BC-PTA improved from 38.0 to 36.7 and from 37.1 to 36.9 dB-HL for mPP and SDT, respectively (Δ –1.3 versus –0.2 dB-HL; p  = 0.077). AC-PTA improved from 66.8 to 47.1 and from 66.3 to 46.5 dB-HL for mPP and SDT, respectively (Δ –19.6 versus –19.7 dB-HL; p  = 0.991). ABG-PTA improved from 28.8 to 10.4 and from 29.1 to 9.6 dB-HL for mPP and SDT, respectively (Δ –18.3 versus –19.5 dB-HL; p  = 0.771). Conclusion: In otosclerosis with MHL and limited satisfaction with HA, mPP appeared as safe and effective as SDT and may be considered a treatment alternative in these patients.